Child Care Experiences Among Dual Language Learners in the United States - Linda M. Espinosa; Doré R. LaForett; Margaret Burchinal; Adam Winsler; Hsiao-Chuan Tien; Ellen S. Peisner-Feinberg; Dina C. Castro (SAGE Publishing, 2017)
Although quality center-based child care is helpful in promoting school readiness for dual language learners (DLLs), little is known about the nonparental child care that young DLL children experience. DLL status is often confounded with immigrant status, ethnicity, and poverty. Using nationally representative data from the Early Childhood Longitudinal Study-Birth Cohort, we examined child care experiences with repeated cross-sectional analyses at 9, 24, and 52 months for DLL and non-DLL children. After accounting for demographic and contextual factors, we found few differences in the quality and type of child care experienced by DLL children and children who hear only English in the home. Child care experiences were more related to country of origin, ethnicity, or immigrant status than DLL status. Nonparental caregivers were more likely to speak the child's home language in home-based care than center care. Findings illustrate the importance of distinguishing among DLL status, socioeconomic status, ethnicity, country of origin, and immigrant status when considering the child care experiences of DLLs.